Single active‐site mutants are sufficient to enhance serine:pyruvate α‐transaminase activity in an ω‐transaminase. (23rd April 2015) - Deszcz, Dawid; Affaticati, Pierre; Ladkau, Nadine; Gegel, Alex; Ward, John M.; Hailes, Helen C.; Dalby, Paul A.
<x xml:space="preserve">Abstract</x> We have analyzed the natural evolution of transaminase structure and sequence between an α‐transaminase serine‐pyruvate aminotransferase and an ω‐transaminase from Chromobacterium violaceum with < 20% sequence identity, and identified the active‐site regions that are least conserved structurally. We also show that these structural changes correlate strongly with transaminase substrate specificity during evolution and therefore might normally be presumed to be essential determinants of substrate specificity. However, key residues are often conserved spatially during evolution and yet originate from within a different region of the sequence via structural reorganizations. In the present study, we also show that α‐transaminase‐type serine‐pyruvate aminotransferase activity can be engineered into the CV2025 ω‐transaminase scaffold with any one of many possible single‐point mutations at three key positions, without the requirement for significant backbone remodeling, or repositioning of the residue from a different region of sequence. This finding has significant implications for enzyme redesign in which solutions to substrate specificity changes may be found more efficiently than is achieved by engineering in all sequence and structure determinants identified by correlation to substrate specificity.